HINGLEY, Richard. Roman Officers and English Gentlemen. The Imperial Origins of Roman Archaeology. Londres e Nova lorque: Routledge, 2000, 224p. ISBN 0415235804 - Funari, Pedro Paulo Abreu (Classica - Revista Brasileira de Estudos Clássicos, 2001)
.